A Phytosterolemic Mixture of Sterols Inhibits Cholesterol Synthesis, Esterification, and Low‐Density Lipoprotein Receptor mRNA Abundance in HepG2 Cells. Issue 2 (17th February 2020) - Davis, April; Cole, Laura K.; Min, Kevin Kyung‐Jun; Chow, Sidney; Choy, Patrick C.; Mymin, David; Hatch, Grant M.
Abstract: HepG2 cells were incubated with a 16.5:1.7:1 ratio of cholesterol:sitosterol:campesterol (CSC), a ratio of the major sterols observed in the plasma of phytosterolemia patients, or with cholesterol alone in combination with [ 14 C]acetate for 24 h and the radioactivity incorporated into lipids determined. Cells incubated with CSC exhibited a 40% reduction in cholesterol esterification ( p  < 0.05) compared to cells incubated with cholesterol alone. In addition, a 17.5‐fold reduction ( p  < 0.05) in total cholesterol (cholesterol plus cholesteryl ester) synthesis from [ 14 C]acetate was observed in cells incubated with CSC compared to cholesterol alone. Low‐density lipoprotein receptor ( LDLR ) mRNA abundance was lower in cells incubated with CSC compared to cells incubated with cholesterol alone. Our results suggest that incubation of HepG2 cells with a ratio of sterols that mimic the plasma concentration seen in phytosterolemia patients reduces cholesterol esterification, total cholesterol synthesis, and inhibits LDLR mRNA abundance. We suggest that future cell and animal‐based work on phytostosterolemia might employ this methodology to serve as a novel paradigm of the disease.